2008
DOI: 10.1093/icesjms/fsn091
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns and diets of wild fish assemblages associated with Mediterranean coastal fish farms

Abstract: Fernandez-Jover, D., Sanchez-Jerez, P., Bayle-Sempere, J. T., Valle, C., and Dempster, T. 2008. Seasonal patterns and diets of wild fish assemblages associated with Mediterranean coastal fish farms. – ICES Journal of Marine Science, 65: 1153–1160. Fish are attracted to floating structures, including coastal cage fish farms, sometimes in dense aggregations. To understand better the influence of aquaculture on wild fish stocks, we carried out seasonal visual censuses around three southwestern Mediterranean farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 32 publications
11
113
1
Order By: Relevance
“…However, some fish have the capacity, to a certain extent, of metabolizing some important FAs. Nonetheless, marine fish are well supplied with biologically active FAs in their natural diet and de novo biosynthesis of LC-PUFA, as mentioned before, is likely to be suppressed in marine carnivores (Tocher 2003) and some herbivores, like Liza aurata (Mourente & Tocher 1993, Sargent et al 2002, which is an important species in wild fish aggregations around Mediterranean farms (Fernandez-Jover et al 2008).…”
Section: Present Knowledge Gapsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, some fish have the capacity, to a certain extent, of metabolizing some important FAs. Nonetheless, marine fish are well supplied with biologically active FAs in their natural diet and de novo biosynthesis of LC-PUFA, as mentioned before, is likely to be suppressed in marine carnivores (Tocher 2003) and some herbivores, like Liza aurata (Mourente & Tocher 1993, Sargent et al 2002, which is an important species in wild fish aggregations around Mediterranean farms (Fernandez-Jover et al 2008).…”
Section: Present Knowledge Gapsmentioning
confidence: 98%
“…A key issue is to quantify the minimum residence time of wild fish around the cages and, therefore, the minimum period and quantity of consumption of food pellets that enables detection of significant changes in the FA composition of fish tissues. Aggregated fish undertake seasonal migra-tions; thus, many species are not resident around the farms throughout the year (Valle et al 2007, Fernandez-Jover et al 2008. It has been estimated that 3 to 4 mo are sufficient time to provoke a substantial change in the FA composition of Mediterranean horse mackerel, which was reflected in a strong increment of linoleic and diminished levels of DHA and the n-3/n-6 PUFA ratio (Fernandez-Jover et al 2007).…”
Section: Present Knowledge Gapsmentioning
confidence: 99%
“…For fish farms, several studies reported increases in abundance and species richness primarily for pelagic fishes with predatory feeding habits, planktivores, and demersal species that consumed food pellets deposited under cages , Valle et al 2007, Fernandez-Jover et al 2008. Research suggests that nutrient enrichment disproportionately increases the dominance of competitively superior species and may hence reduce diversity (Hillebrand et al 2007).…”
Section: Species Richness Responsesmentioning
confidence: 99%
“…For example, there is some evidence to suggest that fish farms disproportionately increase the abundance of pelagic fishes with predatory feeding habits and planktivores , Valle et al 2007, Fernandez-Jover et al 2008. In other habitats and contaminant source groupings, the response of different ecological groups appears to be highly variable and at times contradictory For example, in the Khalaf & Kochzius (2002) study, herbivores, detrivores, and planktivores experienced increased abundance and diversity in association with industrial contamination, while fish that feed on invertebrates or other fish decreased.…”
Section: Linking Contaminant Effects To Fish Ecologymentioning
confidence: 99%
“…Akyol and Ertosluk (2010) recorded ABT at Turkish sea bream and sea bass fish farms. Dempster et al (2002) and Fernandez-Jover et al (2008) observed ABT at two sea bream and sea bass cages sited off the Spanish coast. Moreover, fish farmers and fishermen from various sites around the Mediterranean have reported an increase in the number and frequency of occurrence of aggregated ABT in the vicinity of tuna farms.…”
Section: Introductionmentioning
confidence: 99%